Legality of EndSARS Protest: A Quest for Democracy in Nigeria - Paul Atagamen Aidonojie; Oluwaseye Oluwayomi Ikubanni; Alade Adeniyi Oyebade (Journal of Human Rights, Culture and Legal System, 2022)
An essential hallmark of a democratic society is a statutory institution responsible for protecting (Human Rights) the lives, properties, and catering to its people's needs. However, in Nigeria, there has been an incessant abuse of its citizens' rights by the Special Anti-robbery Squad (SARS) and complaints of low sustainable development, which had trigger the EndSARS protest. Hence, this study's essence is to ascertain the reason for the EndSARS protest and how to salvage the protest. Given this, the study used an online survey questionnaire sent to 363 respondents (randomly selected) residing in the various state of the Federal Republic of Nigeria. Descriptive and analytical statistics were used to analyse 363 respondents’ responses to the questions. The study found that the reason for the EndSARS protest is police brutality and poor sustainable development. The study therefore concludes and recommended concerning its findings that there is a need for the Nigerian Government within the State and at the Federal level to embark on a sustainable development project that will cater to the need of its citizens and also endeavour to curtail police excess in abusing human rights.